Assessing The Impact of Random Drug Testing on The Internal Cleansing of The Philippine National Police in Police Regional Office 12 - Ani, Honorio R.; Alcantara , Jayson B; Cole , Angeline B.; Oriel , Rhona O.; Garcia, Rene; Punzalan , Jerick L; Espina , Madel M; Mobo, Froilan D.; Villa, Elizabeth B. (Future Science / FSH-PH Publications, 2025)
This study assessed the impact of Random Drug Testing (RDT) on the internal cleansing efforts of the Philippine National Police (PNP) in Police Regional Office (PRO) 12. Using a quantitative research design, structured surveys were conducted with 16 PNP personnel across various ranks, designations, and years of service. The study analyzed RDT results from 2020 to November 2024, showing a low overall positivity rate of 0.03%. Most units demonstrated strong compliance, although Sarangani PFU reported two positive cases, and General Santos City Forensic Unit did not conduct any RDTs, highlighting a need for uniform implementation. Respondents strongly agreed on RDT’s role in identifying substance abuse, ensuring fairness, and promoting a drug-free culture. However, privacy concerns were raised by some participants, indicating varying perceptions about the potential invasion of privacy. Statistical analysis revealed no significant differences in perceptions based on rank, designation, or length of service, suggesting a consistent view of RDT's effectiveness across groups. An expert forensic chemist affirmed the reliability of the drug testing protocols. This study provided valuable insights into the benefits and challenges of RDT in enhancing internal discipline within the PNP and offered recommendations for policy improvement and uniform implementation across all units.